Hungary's eurozone entry date: What do the markets think and what if they change their minds? - Attila Csajbók; András Rezessy (Magyar Nemzeti Bank, 2005)
This article investigates the potential impact of a shift in market expectations about a country's eurozone entry date on long-term yields and the spot exchange rate in a simple uncovered interest parity (UIP) framework. The results suggest that the size of the reactions depend on how far the entry date is postponed, how far current inflation is from the Maastricht-satisfying level, and whether the credibility of the central bank's target inflation path is sensitive to changes in the expected entry date. In the empirical part, the authors apply the framework for Hungary and draw some policy conclusions for the timing of ERM II entry.
Keywords: E42; E52; F33; F42; 330; monetary policy; monetary union; expectations; euro zone entry; uncovered interest parity; Eurozone; Europäischer Währungsverbund; Mitgliedschaft; Erwartungstheorie; Wechselkurs; Risikoprämie; Ungarn